Strategies to address inequity of uncorrected refractive error in the Western Pacific: a modified delphi process - McCormick, Ian; Tong, Kelvin; Abdullah, Nurliyana; Abesamis‐Dischoso, Carmen; Gende, Theresa; Hashim, Effendy; Ho, S. May; Jalbert, Isabelle; Jeronimo, Belmerio; Matoto‐Raikabakaba, Elenoa; Ono, Koichi; Piyasena, Prabhath Nishantha; et al. (Wiley, 2024)
Purpose: Uncorrected refractive error is the leading cause of vision impairment globally; however, little attention has been given to equity and access to services. This study aimed to identify and prioritise: (1) strategies to address inequity of access to refractive error services and (2) population groups to target with these strategies in five sub-regions within the Western Pacific. Methods: We invited eye care professionals to complete a two-round online prioritisation process. In round 1, panellists nominated population groups least able to access refractive error services, and strategies to improve access. Responses were summarised and presented in round 2, where panellists ranked the groups (by extent of difficulty and size) and strategies (in terms of reach, acceptability, sustainability, feasibility and equity). Groups and strategies were scored according to their rank within each sub-region. Results: Seventy five people from 17 countries completed both rounds (55%women). Regional differences were evident. Indigenous peoples were a priority group for improving access in Australasia and Southeast Asia, while East Asia identified refugees and Oceania identified rural/remote people. Across the five sub-regions, reducing out-of-pocket costs was a commonly prioritised strategy for refraction and spectacles. Australasia prioritised improving cultural safety, East Asia prioritised strengthening school eye health programmes and Oceania and Southeast Asia prioritised outreach to rural areas. Conclusion: These results provide policy-makers, researchers and funders with a starting point for context-specific actions to improve access to refractive error services, particularly among underserved population groups who may be left behind in existing private sector-dominated models of care.